Time-interleaved quantum random number generation within a coherent classical communication channel - Ferreira, Maurício J.; Pereira, Daniel; Muga, Nelson J.; Silva, Nuno A.; Pinto, Armando N. (Anais do Workshop de Comunicação e Computação Quântica (WQuantum); 2021: Anais do I Workshop de Comunicação e Computação QuânticaDO - 10.5753/wquantum.2021.17225, 2021)
We propose and analyse a suitable setup for a time-interleaved vacuum-based quantum random number generator (QRNG) within a classical communication channel, which removes the need for a dedicated generation device. The experimental setup was characterized to assess the conditions where quantum ﬂuctuations are dominant, and support for generation rates up to 1.3 Gbps is observed. Finally, the random bit stream is subjected to the NIST randomness test suite, consistently passing all evaluations.